GAMBARAN PROSES REGULASI EMOSI PADA PELAKU SELF INJURY - Margaretha, Angelin Adelaide (Universitas Katolik Widya Mandala Surabaya, 2019)
Self-injury is an attempt or an act of hurting oneself. When one’s emotional stability is low, they tend to hurt themselves intentionally, for example by cutting their wrist. Self–injury individual enjoy the action and use it as a medium for emotional release. Emotion regulation is the ability to manage emotions that can be performed by anyone so that they can understand problems correctly and can be calm and think clearly. This study used a qualitative approach, in particular phenomenological method through semi-structured interview to individuals with self-injury behaviorwith the age range of 18-40 years and hadbeen involved in self-injury behavior at least 5 times in the last 12 months without any intention to commit suicide.Data analysis used is inductive analysis. Results showed that individuals who committed self-injury had a desire to release their negative emotions and negative feelings such as anger by seeing their own wound. Both informants received less attention from their parents and showed a lack of communication with their family, thus making both informants unable to express their feelings to others since they were childhood. This made the two informants looked for another way to transfer their negative emotions; that is, by repeating the self injury because they were relieved.